Resolving daily wave 4 nonmigrating tidal winds at equatorial and midlatitudes with WINDII: DE3 and SE2. Issue 11 (21st November 2015) - Cho, Young‐Min; Shepherd, Gordon
Abstract: The Wind Imaging Interferometer observed nonmigrating tidal winds from 90 to 260 km during daytime and at 99 and 250 km during the night and found that the amplitudes and phases of the daytime and nighttime extracted wave 4 for a given day were different, indicating the presence of more than one component. The objective of this study is to resolve those components. Local time versus longitude propagation plots over individual seasons revealed the diurnal eastward propagating wave number 3 (DE3), the semidiurnal eastward propagating wave number 2 (SE2) and the stationary planetary wave number 4 (SPW4). Using a fitting procedure for individual days it was then found possible to determine the amplitudes and phases of DE3 and SE2 and the amplitude of SPW4 for each day, using a constant phase for the SPW4 obtained from the propagation plot. These DE3 and SE2 values were compared with data‐constrained model results yielding good agreement at 99 km but with mixed agreement at 250 km. Time series analysis of 164 days duration showed considerable variability in the amplitudes of the zonal wind for DE3 with the SPW4 tending to follow; DE3 power spectral peaks occurred near 12, 16, and 32 days. The SE2 showed less variability, also displaying spectral peaks but shifted from the DE3 peaks. Monthly averages of the DE3 and SE2 show that the DE3 is predominant at the equatorial mesosphere/lower thermosphere region. On the other hand, the SE2 is uniformly present at lower and midlatitudes and all altitudes. Key Points: Resolving the nonmigrating tides with a single day of thermospheric wind observations Daily and seasonal variations of DE3 and SE2 Thermospheric nonmigrating tides at equatorial and midlatitude region